STRATEGI PENYULUHAN PERTANIAN TERHADAP KETERAMPILAN PETANI PADA KELOMPOK TANI PADI SAWAH MELALUI SISTEM TANAM JAJAR LEGOWO DI KECAMATAN KOTA UTARA KOTA GORONTALO - Suangita, Indriyani Harmain; Bempah, Irwan; Saleh, Yanti (Universitas Negeri Gorontalo, 2024)
The purpose of this study is to identify the internal and external extension factors that affect the improvement of farmers' skills in lowland rice farmer groups using the jajar legowo cropping system in North City District, as well as to identify the agricultural extension strategy for improving farmers' skills in lowland rice farmer groups using the jajar legowo cropping system in North City District. the Jajar Legowo cropping system in the North City District. North City District, Gorontalo District, and Gorontalo Province will be the locations of the research. Researchers used a qualitative approach with a SWOT analysis technique with sampel of 11 extension workers in the North City Disrtict. Based on the results of the study, it can be concluded that the identification of internal and external factors that influence extension agents in improving the skills of farmers through the legowo row cropping system, namely internal factors in the form of management and organization aspects, aspects of facilities and infrastructure, aspects of human resources (HR), and external factors in the form of political aspects, social aspects, and technological aspects, The counseling strategy for developing farmers' skills through the jajar legowo cropping system through the SWOT analysis diagram is in quadrant 1, namely supporting an aggressive strategy or SO (strength-Opportunities) strategy